The Nazi-fascist new order for European culture - Martin, Benjamin George (Harvard University Press, 2016)
During World War II, Nazi-fascist cultural organizations brought writers, filmmakers, and composers together at international conferences where intellectuals celebrated a nationalist and anti-Semitic vision of European culture and pursued the continent-wide reform of the legal and economic bases of European culture. The Nazi-Fascist New Order for European Culture charts the origins, successes, and collapse of the Axis's pan-European cultural institutions. It analyzes their core ideas, charts their internal rivalries, and reveals the complex dynamic of cooperation and competition between the Germans and the Italians that stood at the heart of the project.--